Issues on occupational safety and health at workplace among older fishermen in Malaysia - Hussain, Mohd Rizal; Abdul Rahman, Anita; Mohd Yusuff, Rosnah; Latif, Nabilah; Syed Abdul Rashid, Sharifah Norazizan; Abdullah, Haslinda (National Institute of Occupational Safety and Health (NIOSH), 2014)
The fisheries sector is an important sub-sector in Malaysia and plays a significant role in the national economy development. Fish is largely consumed by the population and the fishery industry is also a source of employment for those living in the coastal areas. However, sea fishing is a dangerous and risky occupation. Previous studies have shown that occupational accidents and injuries among fishermen are prevalent. Thus, this study was conducted to explore occupational safety issues among older fishermen in Malaysia. A total of 397 fishermen age 45 years and above in the states of Terengganu, Kedah and Perak were interviewed by trained enumerator using a questionnaire that focused on the safety problems at work and what are the causes of these problems. Data was analyzed using Statistical Program for Social Science (SPSS). Majority of respondents were male, Malay, married and had primary school education. The finding also showed that almost one-third of the respondents reported that they had experienced boat accidents mostly caused by bad weather. One-fifth of the respondents in this study have experienced accidents/physical injury in their workplace, with animal bites and being stung identified as the main contributor. Falls was reported by almost half of the respondents and slippery floor, strong waves and tripping were identified as the major causes. Few of the identified safety problems among these fishermen such as fall and animal bites are preventable and therefore future improvement can be designed to create a safer and better workplace for the fisheries sectors.